Enhancing the strength of user's authentication using multifactor approach for use in mobile application system - Mohamed, Kartini; Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Nowadays, we can seen many people are occupied with their mobiles almost anywhere and at anytime. Based on statistics by ICT Facts and Figures, about 6.8 out of 7.1 billion people around the world in 2013 are using mobiles compared to only 2 billion in 2005 and this number is still growing (Sanou, 2013). According to another statistics there are more than 50% of all mobile phone users in the market are the smart phone users. It is also estimated that the mobile application system (apps) downloads will be more than 200 million per year by end of 2007 (Shen, 2015). This means that many people are using mobiles especially smart phones because many apps can be downloaded for use by the mobile users. However, the researchers are worried that many of these mobile apps are not properly protected to secure the sensitive or confidential information that might by communicated wirelessly especially those apps that deals with mobile banking, mobile commerce, etc. One of the ways to protect these types of apps is to limit or to control the access to the apps that is the user's authentication. Thus, this study propose a way to enhance the strength of an existing user's authentication with increase number of its multifactor elements and improve its text ciphering technique. Four apps have been developed and two tests namely functionality test and vulnerability test are carried out by an independent testing body to measure effectiveness the proposed enhancements. The results show that the apps have passed all the test which mean that the proposed enhancement have effectively given protections to the apps.